2016
DOI: 10.3917/inno.051.0069
|View full text |Cite
|
Sign up to set email alerts
|

Genre et innovateur frugal : 4 cas de femmes innovatrices

Abstract: L'innovation frugale est un concept très récent défini comme « une solution innovatrice, improvisée, née de l'ingéniosité et de l'intelligence » (Radjou et al, p.23). Bien que provenant des pays émergents, l'innovation frugale prend tout son sens dans un contexte de crise, au point d'intéresser même des entreprises multinationales.Si de très nombreux travaux concernant l'innovation existent depuis des temps immémoriaux, l'innovateur en revanche, n'a pas suscité le même engouement. Ce dernier a connu la même év… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2026
2026

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…By way of example, this return to literature has brought out not only different concepts of the second rank such as empathy, altruism, intuition, local anchoring but also self-confidence, risk aversion and flexibility. The comparison of empirical data with research in management sciences on the link between gender identities and CSR practices revealed that certain aspects had rarely been tackled: in terms of potential and/or effective managerial recompositions, the link between the very masculine portrait of the Schumpeterian entrepreneur-innovator and the frugal innovator close to the female model (Belghiti-Mahut et al , 2016).…”
Section: Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…By way of example, this return to literature has brought out not only different concepts of the second rank such as empathy, altruism, intuition, local anchoring but also self-confidence, risk aversion and flexibility. The comparison of empirical data with research in management sciences on the link between gender identities and CSR practices revealed that certain aspects had rarely been tackled: in terms of potential and/or effective managerial recompositions, the link between the very masculine portrait of the Schumpeterian entrepreneur-innovator and the frugal innovator close to the female model (Belghiti-Mahut et al , 2016).…”
Section: Methodological Approachmentioning
confidence: 99%
“…The various semi-structured interviews that we conducted brought out a certain number of concepts of the frugal innovator: intuition, empathy, altruism and local anchoring, and three other dimensions related to the Schumpeterian acceptance of the entrepreneur-innovator: self-confidence, risk aversion and flexibility (Belghiti-Mahut et al , 2016).…”
Section: Analysis Of Stories Of Life and Practicementioning
confidence: 99%
See 1 more Smart Citation